The Effectiveness of Scimago Mobile Learning to Improve Student Motivation and Learning Outcomes - JIYANTIKA GITADEWI, AISYAH; WIDODO, WAHONO (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
This research aims to describe the effectiveness of Scimago mobile learning on life organization system. The type of research used was research and development (R & D) which is only limited to stage 6, product testing and research design namely One Group Pre-test and Post-test Design. The feasibility of Scimago mobile learning based on effectiveness aspect was obtained from the result of learning motivation questionnaires and student learning outcomes tests. The result of students learning motivation questionnaire shows that there was an increase of gain score between initial and final motivation which is 0.6 with medium category. Moreover, for the student learning outcome, there was an increase of gain score between pretest and posttest which is 0.9 with high category. Consequently, 100% of students were claimed to pass the standard. So it can be concluded that Scimago mobile learning on life organization system is effective to be used as a learning media to increase student motivation and learning outcomes. Keywords: mobile learning, motivation, learning outcomes, life organization system